The Influence of Job Redundancies Toward Intention to Leave with Job Insecurity as the Intervening Variable: A Case Study of a Four-Star Hotel in Indonesia During Pandemic Covid-19 - Efin Shu; Yusuf Ronny Edward (Feedforward: Journal of Human Resource, 2022)
Pandemic Covid-19 has caused the hospitality, travel, and tourism industry around the world to face a major loss. One way to minimize the loss in these sectors is by implementing job redundancies. This option was also implemented by one of the hotels in Pontianak, West Kalimantan, Indonesia. However, job redundancies are not implemented without costs. Employees will experience continuous fear or job insecurity which will result in employees’ willingness to find a new job or intention to leave. Therefore, the purpose of this research is to find out if job redundancies influence the intention to leave with job insecurity as the intervening variable towards the survivors of the redundancy program at the hotel. This research is using the quantitative method as its research approach. The data collection method is conducted by distributing an online questionnaire. The data has passed the validity and reliability tests. The first until third hypotheses tests are using t-test while the fourth hypothesis is using Sobel test. The results of the research show that job redundancies influence job insecurity by 57.9%. Both job insecurity and job redundancies influence the intention to leave by 72%. Finally, job redundancies indirectly influence the intention to leave through job insecurity. The recommendations are to conduct business process re-engineering or service process re-designing to maintain the viability of the business, instead of opting for job redundancies. Job redundancies should be the last resort when previous options are not working as this will affect employee turnover rate in the future.